Value Management in Pesantren-Based University (Grounded Research on AKPAM System of UNIDA Gontor) - Zarkasyi, Hamid Fahmy; Mas’ud, Fuad; Hidayatullah, Rakhmad Agung; Khakim, Usmanul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
University-based Pesantren has a distinctive curriculum that develops and integrates the Pesantren system with its academic-university system. This means that the assessment at pesantren universities does not only apply to the academic side but also the boarding (kepesantrenan) side. If the academic side is assessed through the Cumulative Grade Point Average (GPA)/Indeks Prestasi Kumulatif (IPK), what about the value of boarding school? We explore the Student Activity Assessment Credit Score (Angka Kredit Penilaian Aktifitas Mahasiswa (AKPAM)) system at Darussalam Gontor University. We designed the qualitative study using a grounded theory approach. We found that AKPAM can counted as a system designed to calculate the kepesantrenan scores of UNIDA students; which is one of the process systems in Integrative Human Resource Development (HRD) typical of UNIDA Gontor; as a pesantren-based university. Second, the AKPAM system is proven to be directly proportional to the HRD theory proposed by Richard Swanson. Third, pesantren-based universities have proven to be competitive in terms of education management in this era. We highlight that this study expands the novel HR management pattern in pesantren universities; as indigenous education.